ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP KELAS VII BERBANTUAN VISUAL BASIC APPLICATION FOR EXCEL PADA MATERI PECAHAN - Arni Pebriyanti; Martin Bernard; M. Afrilianto (IKIP Siliwangi, 2023)
The purpose of this research is to study the mathematical thinking skills of junior high school students in solving mathematical problems by using the Problem Based Learning approach on fractional materials. This study is a class action study conducted in class VII B Junior High School Pasundan Sidamulih. This study is a class action study. The subjects in the study were 22 students, 12 male students, and 10 female students. This study was conducted as many as 2 cycles, accompanied by the provision of pretes and postes. The data collection technique carried out in this study uses test instruments in the form of pretes and postes, non-test instruments in the form of observation sheets of student and teacher activities. Based on the analysis obtained the average pretest score of 11.95 and the average postes score of 18.45. The data showed an increase in students' mathematical critical thinking skills by 21.74%.